On Lie Homomorphisms of Complex IntuitionisticFuzzy Lie Algebras (European Journal of Pure and Applied Mathematics, 2024)
In this paper, we investigate the properties of complex intuitionistic fuzzy Lie subalgebras and ideals under Lie algebra homomorphisms, focusing on both images and inverse images. We provide detailed proofs for several new results concerning the preservation of complex intuitionistic fuzzy structures through homomorphisms, and we introduce additional homomorphism-related properties for these structures. This work extends known results to the context of complex intuitionistic fuzzy Lie algebras, contributing new insights into their behavior under algebraic mappings.
Keywords: Lie ideal; Lie algebra homomorphism; complex intuitionistic fuzzy Lie